Geek Girls Inequality and Opportunity in Silicon Valley. - Twine, France Winddance (New York University Press, 2022)
An inside account of gender and racial discrimination in the high-tech industryWhy is being a computer "geek" still perceived to be a masculine occupation? Why do men continue to greatly outnumber women in the high-technology industry? Since 2014, a growing number of employment discrimination lawsuits has called attention to a persistent pattern of gender discrimination in the tech world. Much has been written about the industry's failure to adequately address gender and racial inequalities, yet rarely have we gotten an intimate look inside these companies. In Geek Girls, France Winddance Twine provides the first book by a sociologist that "lifts the Silicon veil" to provide firsthand accounts of inequality and opportunity in the tech ecosystem. This work draws on close to a hundred interviews with male and female technology workers of diverse racial, ethnic, and educational backgrounds who are currently employed at tech firms such as Apple, Facebook, Google, and Twitter, and at various start-ups in the San Francisco Bay area. Geek Girls captures what it is like to work as a technically skilled woman in Silicon Valley. With a sharp eye for detail and compelling testimonials from industry insiders, Twine shows how the technology industry remains rigged against women, and especially Black, Latinx, and Native American women from working class backgrounds. From recruitment and hiring practices that give priority to those with family, friends, and classmates employed in the industry, to social and educational segregation, to academic prestige hierarchies, Twine reveals how women are blocked from entering this industry. Women who do not belong to the dominant ethnic groups in the industry are denied employment opportunities, and even actively pushed out, despite their technical skills and qualifications. While the technology firms strongly embrace the rhetoric of diversity and oppose discrimination in the workplace, Twine argues that closed social networks and routine hiring practices described by employees reinforce the status quo and reproduce inequality. The myth of meritocracy and gender stereotypes operate in tandem to produce a culture where the use of race-, color-, and power-evasive language makes it difficult for individuals to name the micro-aggressions and forms of discrimination that they experience. Twine offers concrete insights into how the technology industry can address ongoing racial and gender disparities, create more transparency and empower women from underrepresented groups, who continued to be denied opportunities.